Direct Determination of Selenium in Serum Matrix by Electrothermal Atomic Absorption Spectrometry: Application on Healthy Individuals from Algeria - Abderrezak Khelfia; Mohammed Azzouz; Rania Abtroun; Mohammed Reggabi; Berkahoum Alamira (Journal of Pharmacy and Nutrition Sciences, 2018)
Selenium is a trace element implicated significantly in oxidative stress in biological systems. In this work, a direct method for selenium determination in serum samples by electrothermal atomic absorption spectrometry with Zeeman background correction is proposed. Serum samples were five-fold diluted in a 0.14% HNO3 and 0.2% Triton X-100 solution. Aliquots of 20 µL of the diluted serum samples were directly introduced into transversely heated graphite tubes. A total of 5 µg Pd and 3 µg Mg(NO3)2 was used as chemical modifier. Optimization of heating program was conducted by varying pyrolysis and atomization characteristic values. The optimal conditions were found to be 1400 and 2000 °C for pyrolysis and atomization temperatures respectively and 11 seconds for pyrolysis hold time. The standard additions method was employed for calibration. Intra-day and inter-day validation using quality control samples at each point of the addition calibration curve were performed. Good accuracy, precision and recovery were achieved with the proposed method (less than 5% for accuracy and precision). A characteristic mass of 92.550 pg, a limit of detection of 4.010 ppb and a limit of quantification of 13.375 ppb in undiluted serum samples were obtained. Several reference values of serum selenium concentrations were reported. As an application of the present method, selenium levels were determined in serum samples collected from 20 healthy individuals from Northern-Center of Algeria. Selenium concentrations ranged from 86.883 to 133.955 ppb with a mean value of 110.824±11.898 ppb.